Kejadian Benign Prostatic Hyperplasia Berdasarkan Faktor Kadar Limfosit dan Tempat Tinggal - Bricareira Bara Presmasitha; Yuni Prastyo Kurniati; Nur Mahmudah; N. Juni Triastuti (Jurnal Ners, 2025)
Benign prostatic hyperplasia (BPH) is a usually abnormality in elderly men. This study aims to explain the influence between residence factors and lymphocyte levels on the incidence of BPH. This study used an analytic observational research design with a cross sectional approach. The population in this study were medical records of histopathology preparations at the PA Laboratory of PKU Muhammadiyah Surakarta Hospital. The sample in this study was medical records of histopathology preparations with a diagnosis of prostate tumor from 2021 to 2024 using the principle technique of total sampling. The research instruments used in this study were laboratory medical records and medical record units at PKU Muhammadiyah Surakarta Hospital. Data analysis techniques in this study include univariate analysis, bivariate analysis using the Chi Square test, and multivariate test using logistic regression test. The results of this study found that there is a significant influence between residence factors and the incidence of benign prostate hyperplasia (P=0.02; OR=7.00). There is no significant correlation between lymphocyte level (%) and the incidence of benign prostate hyperplasia (P=0.040; OR=0,957). The residence variable has a greater influence on the incidence of benign prostate hyperplasia than the lymphocyte level factor.